Assessing the Impact of the COVID-19 Pandemic on Nutrition in Older Adults in Japan: Insights from a Mini-Nutrition Assessment Short Form Survey - Morisaki Naoko; Numata Keizo; Morisawa Hiroyuki (Iberoamerican Journal of Medicine, 2023)
Introduction: The coronavirus disease-2019 pandemic has changed the daily lives of older adults in Japan, requiring them to wear masks and limit their movements. As lifestyle changes affect people's health, it is likely that some changes have occurred in their nutrition, which is the foundation of health. Therefore, this study aimed to examine the nutrition of older adults living at home during the pandemic period and identify the impact of the pandemic. Material and methods: The nutrition of older adults living at home was surveyed using the Mini-Nutrition Assessment Short Form (MNA-SF®). The target population was older adults living at home who were independent or in need of care. Surveys were conducted before and during the pandemic. Associations between the two survey periods and the MNA-SF® (nutrition assessment, sub-item) were analysed using χ-square or Fisher's test. The analysis was conducted separately for independent older adults and older adults in need of care. Results: Regarding nutrition assessment, our survey results indicated that 39.5% of older adults were considered "well-nourished," 46% were "at risk for malnutrition," and 14.5% were "malnourished" during the pandemic period. The analysis showed no significant differences in nutrition assessment by survey period for all participants. However, differences were observed in the sub-items before and during the pandemic. Significant differences were observed in neuropsychological problems and body mass index among independent older adults, and in neuropsychological problems, mobility, and reduced food intake among older adults in need of care. Conclusions: Our results suggest that the pandemic has changed the risk factors for undernutrition among older adults living at home, and that these changed factors may differ in part depending on whether they need care.